Predictors of Emergency Room Access and Not Urgent Emergency Room Access by the Frail Older Adults - Gentili, Susanna; Emberti Gialloreti, Leonardo; Riccardi, Fabio; Scarcella, Paola; Liotta, Giuseppe (Frontiers in Public Health, 2021)
Background. Emergency Rooms (ER) overcrowded by older adults has been the focus of public health policies, during the recent COVID-19 outbreak too. This phenomenon has required a change to the older frail people nursing. Health policies have tried to mitigate the frequent use of ER by implementing community care to meet the older adults’ care demand. The purpose of this study is to investigate the predictors of Emergency Room Access (ERA) and Not-Urgent Emergency Room Access (NUERA) of community-dwelling frail older adults in order to provide indication for out-of-hospital care services. Method. Secondary analysis of an observational longitudinal cohort study was carried out. The cohort consisted of 1246 community-dwelling frail older adults (over 65 years) into the Latium Region in Italy. The ER admission rate was assessed over three years from the administration of the Functional Geriatric Evaluation questionnaire. The ordinal regression model was used to identify the predictors of ERA and NUERA. Moreover, the ERA and NUERA rate per 100 observations/year was analyzed. Results. The mean age was 73.6 (SD ± 7.1) years, and 53.4% were female. NUERAs were the 39.2% of the ER accesses, Robust and Pre-frail individuals (79.3% of the sample) generated more than two third of ER accesses (68.17%) even if Frails and Very Frails showed the higher ER rates per observation/year. The ordinal logistic regression model highlighted a predictive role on ERA of comorbidity (OR = 1.13, p<0.001) and frailty level (OR = 1.29; p<0.001). Concerning the NUERA, social network (OR 0.54, P-value = 0.015) and a medium score of pulmo-cardio-vascular function (OR 1.50, P-value = 0.006) were the predictors. Conclusion. Comorbidity, lack of social support and functional limitations increase both ERA and NUERA rates generated by an older adult’s population. Overall, bio-psycho-social frailty represents an indicator of the frequency of ER accesses. To reduce the number of ER accesses intervention should focus mainly the Robust and Pre-frail needs for prevention and care.